Effects of variations of speed and slope on locomotor system variability during running - El Dash, Ingrid (2019)
Running is achieved by cyclic execution of movements that ultimately allows a person to move. Each cycle is divided into two phases. The first phase is where power is absorbed as the body\'s center of mass is lowered and decelerated. The second being where power is generated and the center of mass is propelled upwards and forwards. Power absorption is primarily done by quadriceps muscles while plantar flexors generate most of the power during push-off phase. Variations in speed and slope are met by adjustments in the same direction of force produced by lower limb muscles and, due to changes in energy expenditure, of heart rate. In this context, analysis of variability offer a non-invasive way to measure how well-adjusted muscles are to cope with variations in demand. Thus, our aim was to investigate the relationship between the variability of contractions of muscles from the quadriceps and plantar flexors with changes in speed and slope and in heart rate. Secondarily, we sought to verify if the patterns observed in a restricted group of subjects could also be noted in a wider population. To answer these questions, we used electromyography to collect data of intervals between successive contractions of vasti and gastrocnemius muscles of seventeen runners across several target runs. These runs were chosen with several different speeds and slopes. Runners were divided into two experimental groups: Experiment 1 contained no restrictions regarding age and fitness level while Experiment 2 did control for these variables. Linear regressions and gradients showed that even though variability estimators correlated negatively to speed and/or slope, they could be better explained by changes in heart rate. Thus our main conclusion was that variability between contractions is inversely proportional to muscle activation, in relation to its maximum capacity. As a consequence, different combinations of speed and slope could result in the same variability despite differences in metabolic profile, as long as the power output remains constant. Due to methodological issues, we could not reach a decisive conclusion regarding the comparison between the more restricted and more heterogeneous groups of volunteers, although results suggest that the runners respond to changes of speed and slope in a similar way regardless of differences in age and fitness level